Peran Pendidikan Islam dalam Membangun Masyarakat yang Bermoral (IAI Sunan Giri Trenggalek, 2025)
Education has a very important role in shaping a person's behavior, especially in shaping a moral society. Islamic education aims to shape individuals who are moral, faithful, have good character and can know what is good and what is bad and can be responsible for their surroundings. As the saying goes, no matter how high our knowledge is, if we are not moral, we will not have a place anywhere. And in this context, the article investigates the role of Islamic education in building a moral society, this study aims to identify Islamic education in building a moral society, a qualitative approach is used to collect data from various sources, such as articles and books, In addition, this article also highlights the importance of character education in building morals.